Investigating the feasibility of establishing an enterprise-project management office (E-PMO) in a military organisation: the South African context - Mnisi, Mulalo Vivian (My University, 2022)
The Project Management Office (PMO) can represent different acronyms interchangeably or all of them simultaneously, depending on its primary focus area. The main purpose of a PMO is to ensure a consistent approach to all projects within the organisation. Many challenges face the traditional PMOs, and organisations are now seeking business solutions to address these issues. The PMOs at a departmental or unit level have delivered value to organisations. However, every organisation should desire to progress from a traditional PMO to an Enterprise-PMO (EPMO) to realise the ultimate value of the EPMO. This study investigated the feasibility of establishing an EPMO for a military organisation. A literature review on the PMO and Defence Acquisition System (DMS) was conducted. Furthermore, interviews were conducted with Defence Project Officers. A comparison of the reviewed literature and data collected from interviews was made to draw the research findings. These findings were discussed and suggested opportunities for improvement were given to the military organisation.
A dissertation submitted in partial fulfilment of the requirements for a Master of Science degree in the field of Industrial Engineering to the Faculty of Engineering and Built Environment, School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2021